Germline pathogenic variants of 11 breast cancer genes in 7, 051 Japanese patients and 11, 241 controls. Issue 1 (December 2018) - Momozawa, Yukihide; Iwasaki, Yusuke; Parsons, Michael; Kamatani, Yoichiro; Takahashi, Atsushi; Tamura, Chieko; Katagiri, Toyomasa; Yoshida, Teruhiko; Nakamura, Seigo; Sugano, Kokichi; Miki, Yoshio; Hirata, Makoto; et al.
Abstract Pathogenic variants in highly penetrant genes are useful for the diagnosis, therapy, and surveillance for hereditary breast cancer. Large-scale studies are needed to inform future testing and variant classification processes in Japanese. We performed a case-control association study for variants in coding regions of 11 hereditary breast cancer genes in 7051 unselected breast cancer patients and 11, 241 female controls of Japanese ancestry. Here, we identify 244 germline pathogenic variants. Pathogenic variants are found in 5.7% of patients, ranging from 15% in women diagnosed <40 years to 3.2% in patients ≥80 years, withBRCA1 /2, explaining two-thirds of pathogenic variants identified at all ages.BRCA1 /2, PALB2, andTP53 are significant causative genes. Patients with pathogenic variants inBRCA1/2 orPTEN have significantly younger age at diagnosis. In conclusion, BRCA1/2, PALB2, andTP53 are the major hereditary breast cancer genes, irrespective of age at diagnosis, in Japanese women. Association between variants in 11 different genes and breast cancer risk has been established and sequencing of these genes is recommended to provide personalized diagnosis, therapy, and surveillance for the high-risk patients and their relatives. Here the authors analyse the frequency of germline pathogenic mutations in these genes specifically in a Japanese population.